Evaluation of osseointegration of dental implant with and without primary stability: An experimental study on sheep - Diyar M. Kheder; Ahmed A. Hayder (Erbil Dental Journal)
Background and objective: Primary implant stability is a prerequisite for reaching and maintaining osseointegration. This study aimed to check the amount of osseointegration of dental implant when placed with and without primary stability, clinically, radiological, and histologically.